Radioactivity : a very short introduction - Tuniz, C. (Claudio) (Oxford : Oxford University Press, 2012)
Radioactivity - the breakdown of unstable atomic nuclei releasing radiation - is a fundamental process in nature, and used to provide important applications in science, medicine, and energy production. But it remains misunderstood and feared. This volume explains the nature and mechanisms of radioactivity.
Includes bibliographical references and index.
Description based on print version record.
Keywords: Radioactivity